Mitophagy-mediated adipose inflammation contributes to type 2 diabetes with hepatic insulin resistance - He, Feng; Huang, Yanrui; Song, Zhi; Zhou, Huanjiao Jenny; Zhang, Haifeng; Perry, Rachel J.; Shulman, Gerald I.; Min, Wang (The Journal of experimental medicine, 2021)
White adipose tissues (WAT) play crucial roles in maintaining whole-body energy homeostasis, and their dysfunction can contribute to hepatic insulin resistance and type 2 diabetes mellitus (T2DM). However, the mechanisms underlying these alterations remain unknown. By analyzing the transcriptome landscape in human adipocytes based on available RNA-seq datasets from lean, obese, and T2DM patients, we reveal elevated mitochondrial reactive oxygen species (ROS) pathway and NF-κB signaling with altered fatty acid metabolism in T2DM adipocytes. Mice with adipose-specific deletion of mitochondrial redox Trx2 develop hyperglycemia, hepatic insulin resistance, and hepatic steatosis. Trx2-deficient WAT exhibited excessive mitophagy, increased inflammation, and lipolysis. Mechanistically, mitophagy was induced through increasing ROS generation and NF-κB–dependent accumulation of autophagy receptor p62/SQSTM1, which recruits damaged mitochondria with polyubiquitin chains. Importantly, administration of ROS scavenger or NF-κB inhibitor ameliorates glucose and lipid metabolic disorders and T2DM progression in mice. Taken together, this study reveals a previously unrecognized mechanism linking mitophagy-mediated adipose inflammation to T2DM with hepatic insulin resistance.